La Terminación del Contrato sujeto a la Ley Orgánica del Sistema Nacional de Contratación Pública debe incluir como causal la falta de Pago oportuno por parte del Estado al Contratista - Yunga Garrochamba, Edison Bladimir (2017)
The Organic Law of the National Public Procurement System brings important innovations such as the use of electronic procedures done not only modernizes administrative contracting, but it adapts to modern social reality and the system of globalization and the removal of trade barriers, which facilitates and promotes the participation of more suppliers, in particular the National which improves production processes. Efficiency and economy of the state. However, despite having great advantages in Government Procurement, it is also true that it is necessary to deepen in treatment, Scanning for improvement, because the law is not determined clearly that a contractor can finish unilaterally a contract for lack of timely payment by contracting entities and officials who fail to comply with the provisions of the contract by improper payment of payroll punish the contractor. This thesis aims to reforms, so that the contractor can terminate a contract unilaterally by lack of timely payment by contracting entities and the unilateral termination of the contract for the contractor to declare terminated or advance and unilaterally contracts: for breach of the contracting entity with regard to timely payment; for cessation or delay in payment, or other institutional aspects that affect being paid to the contractor or seriously affect the performance of the contract; There are other aspects that I consider to be 5 established as a permanent physical disability of the contractor, if a natural person, or dissolution of the legal person of the contractor